Transforming Entrepreneurship Education Through Islamic Values: A Needs Assessment at an Islamic Higher Education Institution in Indonesia - Widia Yunita; Yenni Rozimela; Yetti Zainil (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study conducts a needs assessment to support the development of Islamic value-based edupreneurship teaching materials for English Education students at STAI Hubbulwathan Duri. Specifically, it investigates students’ perceptions, needs, and expectations regarding the integration of Islamic values into entrepreneurial learning. Using a quantitative survey design, data were collected from 111 students through a questionnaire grounded in Albert Bandura’s Social Cognitive Theory. The findings reveal that students strongly recognize the importance of aligning business practices with Islamic ethics and aspire to an entrepreneurial identity that is spiritually meaningful, seeing business as a form of da’wah and social empowerment. However, they also identified shortcomings in current learning materials, including insufficient practical guidance, limited exposure to role models, and the absence of value-based assessment methods. These results highlight an urgent need for redesigned coursebooks that incorporate contextual case studies, hands-on learning opportunities, and evaluation approaches rooted in Islamic principles. As a needs assessment, this study concludes that a revised curriculum is essential for fostering competent, ethical, and socially responsible Muslim edupreneurs.